2021
DOI: 10.4103/ijo.ijo_1525_21
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric diabetic retinopathy

Abstract: Increasing prevalence of diabetes mellitus warrants recognition of factors related to asymmetric diabetic retinopathy (DR). This thematic synthesis based on an iterative literature review conducted in Medline and Google Scholar pertaining to diabetes with coexistent asymmetry of retinopathy included 45 original articles, 21 case reports and series, and 18 review articles from 1965 to 2020. Asymmetric DR is defined as proliferative DR (PDR) in one eye and nonproliferative, preproliferative, background, or no DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 72 publications
0
12
0
5
Order By: Relevance
“…Little is known about inter-ocular symmetry and disease predominance or progression. Despite this, inter-ocular asymmetry was proved in other studies although its pathogenic mechanism is currently unclear, requiring further investigation [ 37 , 38 ]. The fluid accumulation in the macula is presumed to be caused by an osmotic disequilibrium with the increase in permeability of the retinal–blood barrier (RBB) and the development of neovascularization [ 6 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about inter-ocular symmetry and disease predominance or progression. Despite this, inter-ocular asymmetry was proved in other studies although its pathogenic mechanism is currently unclear, requiring further investigation [ 37 , 38 ]. The fluid accumulation in the macula is presumed to be caused by an osmotic disequilibrium with the increase in permeability of the retinal–blood barrier (RBB) and the development of neovascularization [ 6 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia activates VEGF and cytokines (TNFα), closing this vicious circle. The disruption of the BRB, intricate subcellular mechanisms (increased oxidative stress by reactive oxygen species, cellular signaling), associated vascular risk factors (atherosclerosis), as well as the clinical course of the disease and other unknown factors could possibly influence the rate of development and severity of DME or DR in one eye more than in the contralateral one [ 38 , 39 ]. On the other hand, studies have shown that anti-VEGF treatment for DME in one eye influenced positively the fellow eye, having good results at follow-up [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a complex and multifactorial syndrome, DM is characterized by numerous symptoms, signs and complications [ 36 ]. Along with diabetic neuropathy and nephropathy, DR can be defined as a microangiopathy that occurs as a result of prolonged diabetes [ 37 , 38 ]. Several intra- and extravascular factors are involved in the pathogenesis of DR, with subsequent capillary closure and decreased blood flow and oxygen to the retina.…”
Section: Major Retinal Diseases and Oxidative/nitrosative Stressmentioning
confidence: 99%
“…Usually, DR is a symmetrical condition, but a form of asymmetric DR has been identified in about 5–10% of cases. In this condition, one eye shows proliferative DR, while a form of non-proliferative, pre-proliferative or no DR is observed in the other eye for at least 2 years [ 37 ]. As discussed previously, several factors are at play in DR: neurodegeneration, involvement of MGC, inflammation and, last but not least, OS [ 17 ].…”
Section: Major Retinal Diseases and Oxidative/nitrosative Stressmentioning
confidence: 99%
“…In recent years, the incidence of diabetes has been increasing in China, and now, it has become the country with the largest number of people with diabetes in the world. It is well known that the danger of diabetes is mainly in its complications, and diabetic retinopathy (DR) is one of the most common diabetic microvascular complications and the leading cause of visual impairment and irreversible blinding disease in the working population [ 3 , 4 ]. The development of DR is associated with a variety of risk factors as well as biomarkers.…”
Section: Introductionmentioning
confidence: 99%